Multilevel Encrypted Text Watermarking on Medical Images Using Spread-Spectrum in DWT Domain - Singh A.K.; Dave M.; Mohan A. (My University, 2025)
This paper presents a secure multilevel watermarking scheme in which the encrypted text acts as a watermark. The algorithm is based on secure spread-spectrum technique for digital images in discrete wavelet transform (DWT) domain. Potential application of the proposed watermarking scheme is successfully demonstrated for embedding various medical watermarks in text format at different subband decomposition levels depending upon their performance requirements. In the embedding process, the cover CT Scan image is decomposed up to third level of DWT coefficients. Different text watermarks such as personal and medical record of the patient, diagnostic/image codes and doctor code/signature are embedded into the selective coefficients of the second and third level DWT for potential telemedicine applications. Selection of DWT coefficients for embedding is done by column wise thresholding of coefficients values. Also, encryption is applied to the ASCII representation of the text and the encoded text watermark is embedded. The algorithm correctly extracts the embedded watermarks without error and is robust against numerous known attacks without much degradation of the medical image quality of the watermarked image. © 2015, Springer Science+Business Media New York.